Comparability of Internet and Telephone Data in a Survey on the Respiratory Health of Children. Issue 1 (2012) - Plante, Céline; Jacques, Louis; Chevalier, Serge; Fournier, Michel
Abstract : BACKGROUND: Mixing survey administration modes has generated concern about the comparability of responses between modes. OBJECTIVE: To explore the differences in respondent profiles, and responses between Internet and telephone questionnaires in a survey on respiratory diseases. METHODS: The data were generated from a mixed Internet and telephone survey of respiratory diseases among children in Montreal (Quebec), in 2006. Comparison of 12 selected questions was performed after standardization for respondent education and income. Stratification of analysis on education and income categories was also performed for the questions with significantly divergent responses. RESULTS: Six questions showed significant differences in responses between modes after standardization. The largest differences among the closed-ended questions were observed for highly prevalent symptoms, dry cough during the night (difference of 9% for positive answer [P<0.01]) and symptoms of allergic rhinitis (difference of 7% for positive answer [P<0.01]). A large discrepancy was also found in the multiple choice question and with an open-ended response (ie, free answer). For the three potentially sensitive questions, a desirability bias was probably present in one question on smoking habits (difference of 2.6 % for positive answer [P<0.05]). CONCLUSION: The differences observed between Internet and telephone responses to selected questions were not completely explained by socioeconomic disparities among the respondents. In a mixed-mode survey (Internet and telephone), caution should be used when formulating sensitive, complex, open-ended and long-ended questions, and those related to highly prevalent and nonspecific symptoms.